2019
DOI: 10.21873/anticanres.13689
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Harvesting for Adoptive Tumor Infiltrating Lymphocyte Therapy in Metastatic Melanoma

Abstract: Background/Aim: Adoptive transfer of tumorinfiltrating lymphocytes (TILs) combined with nonmyeloablative chemotherapy (NMA) has been shown to prolong survival in patients with metastatic disease. Materials and Methods: Tissue harvesting was performed form a variety of sites. TILs were isolated, expanded and infused with bolus high-dose IL-2. Results: Between 2008 and 2018, 242 lesions were resected for TILs harvesting from a range of sites form 196 patients without mortality and with minimal morbidity. Of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The data revealed that although αPD-1 treatment increased expression of the PDCD1 and αPD-L1 elevated expression of all three genes, none of the changes reached statistically significant level compared to the untreated controls based on student's t -test analysis (Figure 5 G). It was previously indicated that IL-2 expanded tumor-infiltrating lymphocytes (TILs) and has remarkable efficacy in immunogenic tumors 40 , we herein tested combinatory effects of αPD-1 and IL-2 in our 3D-TSC system (Figure 5 H, I). The data indicate that combinatory treatment on 3D-TSCs derived from a mouse SPC (658) cancer elicited higher killing effect than the mono-treatment, yet the enhancement did not reach a statistically significant level (Figure 5 H).…”
Section: Resultsmentioning
confidence: 99%
“…The data revealed that although αPD-1 treatment increased expression of the PDCD1 and αPD-L1 elevated expression of all three genes, none of the changes reached statistically significant level compared to the untreated controls based on student's t -test analysis (Figure 5 G). It was previously indicated that IL-2 expanded tumor-infiltrating lymphocytes (TILs) and has remarkable efficacy in immunogenic tumors 40 , we herein tested combinatory effects of αPD-1 and IL-2 in our 3D-TSC system (Figure 5 H, I). The data indicate that combinatory treatment on 3D-TSCs derived from a mouse SPC (658) cancer elicited higher killing effect than the mono-treatment, yet the enhancement did not reach a statistically significant level (Figure 5 H).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the unique nature of ACT as an autologous transfer of antitumor‐directed lymphocytes, a suitable site for tissue procurement is obligatory. Though a preferable choice would logically be a cutaneous or soft tissue lesion, deep visceral metastases may be the only sites of persistent disease, with prior work suggesting no differences in fold expansion between sites, including subcutaneous, nodal tissue, lung, and visceral organs 12 . While it may have been historically presumed that thoracic surgical procedures carry greater risk and complication rate than harvest from other body cavities, such as the abdomen or pelvis, it is important to recognize that commonly cited risk profiles for thoracic surgical procedures are reflective of the typical patients undergoing surgery for lung or esophageal cancer—who are often older, long‐term smokers, with many additional comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…As such, there is great interest in shortening the wait time from clinical decision to treat with TIL until the product is available for infusion. One approach is TIL harvest at an earlier time point prior to when the product might actually be needed (67). TILs might be stored either as the frozen tumor sample or a manufacturing intermediate and the sample will be ready for rapid completion of manufacturing at the time when clinically indicated (68,69).…”
Section: Banking Modelsmentioning
confidence: 99%